Different aggregation ways. We have designed four aggregation approaches to fuse the outputs of axial-free attention layers, which are common in other network architectures. “**" denote significance levels of , from a two-sided paired t-test when comparing our best model with others. The best results are shown in bold. - Hua Wang (13530) (2025)
Different aggregation ways. We have designed four aggregation approaches to fuse the outputs of axial-free attention layers, which are common in other network architectures. “**" denote significance levels of , from a two-sided paired t-test when comparing our best model with others. The best results are shown in bold.